The Effectiveness of Pop Up Book and Hand Puppets Media on Toothbrushing Skills of Slow Learner Students - Silvia Prasetyowati; Afidatul Mukhlishoh Edi; Siti Fitria Ulfah; Isnanto Isnanto (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2023)
Slow learner children are a group of children with an IQ of 70-90 who experience difficulties in adapting, responding to stimuli, and thinking. The impact of these barriers is the inability to perform self-care such as taking care of yourself and brushing your teeth properly. There are 14% of slow learner children in Indonesia and 80.64% of them have poor oral hygiene caused by improper brushing. One effort that can be done is to conduct counseling about brushing teeth using appropriate media, namely pop-up book media and hand puppets. The problem in this research is that the slow learner students' brushing skills are still in the bad category. This study aims to determine the effectiveness of pop-up book media and hand puppets on the teeth-brushing skills of slow-learner students. This type of research is a Quasy Experiment with a pretest-posttest design, with a population of 20 slow-learner students. The data collection instrument used was an observation sheet. The data analysis technique uses the Wilcoxon test and the Mann-Whitney test. The results showed that there were differences in the effectiveness of pop-up book media and hand puppets on the teeth brushing skills of slow learners grades 3-5 in the inclusion class of SDN Mojo III and SDN Airlangga I Surabaya City after 21 days of observation.